A Rural Resort: Farming and Recreation in Scott County, Kansas at Beaver Beach, 1886-1933 - Kirk, Patrick (Kansas State University, The Chapman Center for Rural Studies, 2010)
The author uses historic accounts to recreate the details of Beaver Beach Amusement Park, which was a source of recreation for rural Scott County residents.
Patrick Kirk, “A Rural Resort: Farming and Recreation in Scott County, Kansas at Beaver Beach, 1886-1933,” Chapman Center Research Collections, accessed October 7, 2020, https://ccrsresearchcollections.omeka.net/items/show/221.
Keywords: Alva Johnson; Beaver Beach; Beaver Creek; Homestead Act; Scott County; Smoky Hill River